2013
DOI: 10.1038/ngeo1889
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behaviour of the East Antarctic ice sheet during Pliocene warmth

Abstract: We interpret this erosion to be associated with retreat of the ice sheet margin several hundreds of kilometres inland and conclude that the East Antarctic ice sheet was sensitive to climatic warmth during the Pliocene.Recent satellite observations reveal that the Greenland and West Antarctic ice sheets are losing mass in response to climatic warming 6 . Basal melting of ice shelves by warmer ocean temperatures is proposed as one of the key mechanisms facilitating mass loss of the marine-based West Antarctic ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
295
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 276 publications
(317 citation statements)
references
References 28 publications
19
295
2
1
Order By: Relevance
“…We investigate how this uncertainty affects simulations of mid-Pliocene warm period ice sheet dynamics, as this is a period with atmospheric CO 2 concentrations similar to the present (400 ppm) [Seki et al, 2010] with evidence for large-scale retreat of both the West and East Antarctic ice sheets Cook et al, 2013;Raymo et al, 2011]. Although we explore ice sheet sensitivity to bedrock elevation uncertainty for a mid-Pliocene climate forcing, these uncertainties are also relevant to simulations of future ice sheet dynamics for a projected warmer climate [Collins et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…We investigate how this uncertainty affects simulations of mid-Pliocene warm period ice sheet dynamics, as this is a period with atmospheric CO 2 concentrations similar to the present (400 ppm) [Seki et al, 2010] with evidence for large-scale retreat of both the West and East Antarctic ice sheets Cook et al, 2013;Raymo et al, 2011]. Although we explore ice sheet sensitivity to bedrock elevation uncertainty for a mid-Pliocene climate forcing, these uncertainties are also relevant to simulations of future ice sheet dynamics for a projected warmer climate [Collins et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…2). Isotopic Nd and Sr provenance indicators suggest that the terrigenous components in these diatomrich/bearing muds are associated with periods of glacial retreat of the ice margin back into the Wilkes Land Subglacial Basin during the Early Pliocene 17 . The Antarctic ice sheet loses the majority of its mass via iceberg calving and sub-ice-shelf melting 18 , which are intimately linked because enhanced ice-shelf melt leads to reduced buttressing, that in turn acts to enhance the flow of glacial tributaries, ultimately enhancing iceberg discharge 19 .…”
mentioning
confidence: 99%
“…Geologic records 7,9,17 and model simulations 8 of past warm climates highlight the sensitivity of the marine-based portions of the Antarctic ice sheets to ocean warming. However, the mechanism by which the coastal ocean warms and destabilizes marine grounding lines, particularly in response to obliquity forcing, remains elusive.…”
mentioning
confidence: 99%
“…Instead, the sea-floor sediments revealed that the ice sheet waxed and waned many times between 5.3 million and 3.3 million years ago 7 -an epoch called the Pliocene, when air temperatures were up to 2 °C higher than today. "We got a clear signal every time it was warm, suggesting that the ice sheet was sensitive to climate warming, " says van de Flierdt.…”
Section: Troubled Pastmentioning
confidence: 99%